Designing A Website-Based Cash Flow Accounting Information System Using Php and Mysql at Raudhatul Atfal - Dewi, Annisa Ammyla; Supriyati (International Journal of Research and Applied Technology (INJURATECH), 2025)
This study aims to design a web-based cash flow accounting information system to address the issue of manual financial record-keeping still applied at Raudhatul Atfal Khalidya. The system was developed using the Waterfall model, which includes stages of needs analysis, design, implementation, testing, and maintenance. Data were collected through observation, interviews, documentation, and literature review. The results show that the system successfully replaces manual processes with digital ones, minimizes recording errors, accelerates reporting, and improves the accuracy and transparency of financial information. The system follows the ISAK 35 standard and generates cash flow reports based on operating, investing, and financing activities. Using PHP and MySQL technology, the system can be accessed flexibly and in real time by authorized personnel. This research provides practical contributions for nonprofit educational institutions to manage finances more effectively.